Development of Web-Based Learning Media: Physical Education, Sports, and Health (PJOK) Volleyball Subjects - Hendrik Hasibuan; R Mursid; Dewi Endriani (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of this research is to determine the feasibility of web-based learning media in the PJOK volleyball subject and the effectiveness of web-based learning media in the PJOK volleyball subject. The research uses the ADDIE Research and Development model approach (Analysis, Design, Development, Implementation, and Evaluation). The research results show: (a) web-based learning media from media expert validation with a score of 4.45, 89%, very feasible category; design expert validation with a score of 4.6 percentage 92%, very feasible category; material expert validation with a score of 4.5 percentage 90%, very feasible category; individual student trials with a score of 4.3, percentage 86%, very high category; student group trials with a score of 4.5, with a percentage of 90%, very high category. (b) The effectiveness of web-based learning media shows that there is a significant difference between student learning outcomes in experimental classes and classes without using web-based learning media at a significance level of 0.05 or 5%. The results of the T-test calculations on the posttest scores for the experimental class and control class show tcount > ttable, namely 3,225 > 1,677. It is evident from the average value of the posttest learning results for the experimental class that it is 88% higher than the posttest learning results for the control class at 64%. Thus, it can be concluded that the web-based learning media developed is effectively used to improve student learning outcomes.